Geology and sedimentology of the Upper Devonian Escuminac Formation, Quebec, and evaluation of its paleoenvironment: lacustrine versus estuarine turbidite sequence - Hesse, Reinhard; Sawh, Hemdat (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1992)
The Escuminac Formation of-the Upper Devonian Miguasha Group at the western end of Chaleurs Bay, Quebec, famous for its fossil fish fauna, is a turbidite sequence whose environment of deposition has been a matter of debate. Interpretations vary with different authors between lacustrine or brackish to coastal marine. It is possibly of estuarine origin. Its total stratigraphic thickness of 117 m has been divided into eight lithostratigraphic units on the basis of vertical changes in sands tone: shale ratio. A lacustrine setting is feasible in view of the association with fluvial formations below (Fleurant Formation) and above (Bonaventure Formation), although these are separated by a disconformity or an angular unconformity from the Escuminac. The lack of any shelly marine invertebrate fauna is negative evidence indirectly favoring a lacustrine origin. Periodically stagnant bottom-water conditions evidenced by the preservation of laminites are compatible with a lake environment. The fossil fish fauna, however, contains elements which point toward brackish or marine environments. Geochemical evidence also seems to support brackish conditions, although it is not clear to what extent the geochemical signature may have been inherited from older marine detrital clays. A silled estuary would best accommodate the different lines of evidence, but poses problems of fitting into the broadscale paleogcographic picture of the Upper Devonian Old Red Continent.